A Study of the Causality Between Convertible Bond Prices and Stock Prices in Conversion‐price Reset Periods—Time‐series and Cross‐section Analyses. (June 2015) - Wang, Ma‐Ju; Lin, Yun‐Wei; Lee, Tsun‐Siou
Abstract This study examines the causality between the returns of convertible bonds and stocks during periods of conversion‐price resets and general pre‐reset in Taiwan. Profits, stock turnover, and firm size affect the significance of causality. The empirical results indicate that the returns of convertible bonds always lag behind the stock returns for general pre‐reset periods. However, for reset periods, the numbers of companies for which convertible bonds lead ahead of the stock market increases. The causality reversal is based on uprising liquidity and information transparency. These results provide evidence that various reset price mechanisms affect financing market efficiency.